Permainan Tradisional Gasing sebagai Warisan Budaya Lokal di Labuhan Haji - Dwi Zahara; Buleng Sinaga (Lembaga Publikasi Ilmiah Nusantara, 2026)
Traditional games are an important part of local cultural heritage, carrying educational, social, and historical values for the community. One traditional game that is still known among coastal communities in East Lombok is the spinning top (gasing). However, technological advancements and changes in children’s play patterns have caused traditional games to be played less frequently. This community service activity aims to preserve the traditional game of gasing as a form of local cultural heritage and to increase public awareness—especially among the younger generation—of the importance of safeguarding regional culture. The implementation methods include socialization, game demonstrations, training in making and playing gasing, and organizing gasing competitions involving children, teenagers, and community leaders. The activity was carried out in Labuhan Haji Village using a participatory approach that actively involved the community at every stage. The results show an increase in knowledge and interest among the community regarding the traditional game of gasing. Children and teenagers, who previously spent more time playing digital games, have begun to show interest in learning and playing gasing as a recreational activity as well as a means of learning values such as togetherness, sportsmanship, and local wisdom. In addition, this activity strengthens the role of the community in preserving and passing down local culture to future generations. Thus, the traditional game of gasing serves not only as a form of entertainment but also as a medium for education and cultural preservation in Labuhan Haji Village. This community service initiative is expected to serve as a model for efforts to preserve traditional games in other regions.